(6-4i)/(3-i)
=(6-4i)(3+i)/[(3-i)(3+i)]
=(22-6i)/10
=11/5 - 3i/5
------------
snowy,
[(3-i)(3+i)] = 9-i^2 = 10
2006-12-30 07:49:11
·
answer #1
·
answered by sahsjing 7
·
1⤊
0⤋
First, you need to make the denominator a real number.
You do that by multiplying both the numerator and the denominator by the conjugate of the denominator (which would be 3 + i). In other words:
(6 - 4i) / (3 - i)
= (6 - 4i)(3 + i) / (3 - i)(3 + i)
= (18 + 6i - 12i -4i^2) / (9 - i^2)
= (18 - 6i + 4) / (9 + 1)
= (22 - 6i) / 10
= 11/5 - (3/5)i
2006-12-30 15:47:28
·
answer #2
·
answered by Rev Kev 5
·
0⤊
0⤋
I assume that "standard form" in this case means that you would not have an "i" in the denominator of your fraction. To simplify that, you would use the "difference of two squares".
(6-4i)/(3-i) * (3+i)/(3+i)
=(6-4i)(3+i)/(3-i)(3+i)
=[18 - 12i + 6i - 4(-1)]/[9-(-1)]
=(22-6i)/10
= (22/10) - (3/5)i
= 2.2 - 0.6i
Hope that helps.
2006-12-30 15:51:01
·
answer #3
·
answered by Tim P. 5
·
0⤊
0⤋
To clear the denominator, we multiply numerator
and denominator by the conjugate of 3-i or 3 + i.
This gives us
(6-4i)(3+i)/10
= (22-6i)/10 = (11-3i)/5.
2006-12-30 16:58:28
·
answer #4
·
answered by steiner1745 7
·
1⤊
0⤋
(6-4i)/(3-i) multiply numerator & denominator by 3+i
(6-4i)(3+i)/(9-i^2) use FOIL
(18+6i-12i-4i^2)/10
(18-6i+4)/10
2.2-.6i or
-.6i+2.2
2006-12-30 16:20:06
·
answer #5
·
answered by yupchagee 7
·
0⤊
0⤋
76
2006-12-30 15:54:40
·
answer #6
·
answered by Dowon Q 4
·
0⤊
1⤋
multiply the numerator and denominator by 3+i
2006-12-30 15:52:37
·
answer #7
·
answered by iyiogrenci 6
·
0⤊
0⤋
(6-4i)/(3-i)
= (6 - 4i)(3 + i)/[(3 - i)(3 + i)]
= (18 - 12i + 6i + 4)/[9 - 3i + 3i + 1], please note i^2 = -1
= (22 -6i)/10
= 2.2 - 0.6i
= -0.6i + 2.2
2006-12-30 15:51:28
·
answer #8
·
answered by Sheen 4
·
0⤊
0⤋
(6-4i)(3+i)/((3-i)(3+i)
=(18+6i-12i+4)/(9-1)
=(22-6i)/8
=11/4-3/4i
2006-12-30 15:47:34
·
answer #9
·
answered by snow l 3
·
0⤊
0⤋